Factors Correlated to Body Fat Percentage, Bone Density, Muscle Mass, and Muscle Strength in Women Practicing Zumba and Aerobics Exercise - Alifah, Istinur; Kusumaningrum, Tiyas; Nastiti, Aria Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Many believe that practicing Aerobics or Zumba helps lose weight and increase muscle strength. The purpose of this study was to analyze factors correlated to body fat percentage, bone density, muscle mass and strength in women practicing Zumba and Aerobics exercise. This study was a correlational study targeted at women practicing Aerobics or Zumba exercise. There were 114 participants selected through inclusion and exclusion criteria. Factors being investigated were Body Mass Index (BMI), milk and supplements consumption, parity, breastfeeding history, frequency of exercise, the length of participation for Zumba and Aerobics exercise, and other physical exercise activity. The data were collected using questionnaires, Bio impedance Analysis TANITA BC-541 and Wall Sit Test (WST). Data were analyzed using Spearman’s Rho Test and Mann Whitney with a significance level of α=0.05. Results showed that factors correlated to body fat percentage were parity, breastfeeding history, frequency of exercise, the length of participation, also other physical exercise activity (p<0.05; r>0.28). Factors correlated to bone density were milk and supplements consumption, breastfeeding history, and frequency of exercise (p<0.05; r≤2.1). Factors associated with muscle mass and strength were BMI, frequency of exercise, and practicing other physical exercise (p<0.05; r>0.25). From these data, it was concluded that not all factors studied were related to body fat percentage, bone density, muscle mass and strength. However, the results of this study also show that the frequency of exercise per week correlates with all dependent variables. This shows that practicing Zumba or Aerobics can improve women’s fitness.